Sosialisasi Kesehatan Prekonsepsi pada Remaja melalui Video - Luh Ani; Arimogi I Komang; Merdana I Made; Sri Darmayani IGA; Arya Utami Ni Wayan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Preconception health is the provision of biomedical services, behavioral and social health interventions for women and partners before conception occurs. Adolescents are a group that is prone to early pregnancy and/or unplanned and unwanted pregnancies. So early prevention needs to be done through increasing adolescent knowledge about preconception health. This service was carried out in July 2020 for teenagers in Sidemen Karangasem District, Bali Province. Socialization materials are arranged videos that are uploaded to youtube media. Furthermore, the youtube media link was distributed to the target by whatsapp group number. All participants were told to answer questionnaires distributed before and after socialization activities carried out through pretests and posttests. The preconception health video has been watched by 119 visitors, receiving 42